2019
DOI: 10.1055/s-0039-1695800
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of an Integrated, Patient-Focused Electronic Health Record Display for Emergency Medicine

Abstract: Background Hospital emergency departments (EDs) are dynamic environments, involving coordination and shared decision making by staff who care for multiple patients simultaneously. While computerized information systems have been widely adopted in such clinical environments, serious issues have been raised related to their usability and effectiveness. In particular, there is a need to support clinicians to communicate and maintain awareness of a patient's health status, and progress through the ED plan of care.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…Over the last decade, the emergence of integrated emergency department information systems (EDISs) has changed emergency department (ED) administration and data management 7,8 . Multiple studies have reported the advantages of EDIS, such as improvement of usability, 9 study recruitment, 10 visual representations, 11 and data collection 12 . Several studies have utilized artificial intelligent algorithms to automatically extract structured information from clinical notes in EMRs 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, the emergence of integrated emergency department information systems (EDISs) has changed emergency department (ED) administration and data management 7,8 . Multiple studies have reported the advantages of EDIS, such as improvement of usability, 9 study recruitment, 10 visual representations, 11 and data collection 12 . Several studies have utilized artificial intelligent algorithms to automatically extract structured information from clinical notes in EMRs 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Want et al, [13] study concerned work-centered usability methods to evaluate integrated patient-focused status displays for Emergency Department (ED) communication and situational awareness. The study uses multiple design methods to show ED data in a prioritized and highly cognitively supporting way, using focus groups, surveying, and scenario-based study.…”
Section: Discussionmentioning
confidence: 99%
“…Providing context to alerts is critical. Effort in the field is being directed towards designing integrated displays that provide necessary context for practitioners (Wang, 2019). Interpretable models naturally align with this push for context, as they provide such context along the path towards explaining their outputs.…”
Section: Discussionmentioning
confidence: 99%